Levels and Human Health Risk Assessment of Heavy Metals in Some Vegetables in Farmer's Field, Jos North, Plateau State Nigeria - E. Oiganji; J. Ichor; J. U. Unimke; R. Z. Lenka (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to evaluate levels and human health risk assessment of heavy metals in some vegetables in farmers’ field, Jos North, Plateau State Nigeria; using X-ray fluorescence (XRF) spectrometry. The evaluation of the average daily intake for adults revealed that Ni in lettuce and cabbage exceeded the permissible levels (0.0094 mg/kg/day), Cr(0.0035mg/kg/day) and Cd(0.0012mg/kg/day) also exceeded safety limits in lettuce. For children, the average daily intake revealed that Pb exceeded permissible limits in celery, cauliflower, and onions, while Cd and Cr levels surpassed the permissible limits in all vegetables, whereas Fe and Zn remained below the DOR permissible limits. The hazard quotient analysis indicated that Cd in lettuce (2.4514) and Cr in lettuce (1.1629) posed significant non-carcinogenic risks for adults. Pb in onions, cauliflower, and celery, Cd and Cr in all vegetables—particularly lettuce—and Ni in lettuce, onions, spinach, cabbage, and celery all had hazard quotients exceeding1, indicating significant health risks for children. The cancer risk analysis showed that both Pb and Cd posed potential risks for both adults and children, with the highest cancer risk observed for Cd in children consuming lettuce (0.00006683). The findings reveal that the daily intake of Pb, Cd, Cr, and Ni—especially in children—poses substantial health risks. Addressing these risks requires urgent implementation of regular monitoring, contamination control measures, and education on safe farming practices to protect vulnerable populations from potential long-term exposure.